(untitled) (GEOmedia, 2015)
The course concern a post graduate diploma for Surveyors wanted by the Ministry of Education, University and Research (MIUR), the Ligurian Region, the Provincial College Surveyors of Genoa and the Naval Academy of Genoa, in order to train professionals’ figure able to manage in a qualified way the main activities related to the management of coastal areas both marine, river and lake, to the protection and safeguarding of coasts, ports and artifacts and, again, in order to create maintenance operations and realization that take account of the adjustments and functional evolution of maritime transport.